The Smithsonian guides to historic America : - Muse, Vance (Stewart, Tabori & Chang, 1998)
The second revised edition in the SMITHSONIAN GUIDES series. A presentation of American historic sites and museums in Northern New England. Features up to date site information which includes location, visiting hours, phone numbers and fee information. Maps and illustrations are included.